PREVALENSI HELMINTIASIS PADA SISWA KELAS 1 – 6 SEKOLAH DASAR MANYAR SABRANGAN SURABAYA TAHUN 2020 - Yauwan Tobing Lukiyono; THOMAS - SUMARSONO; imma rachmawati murhadjito (Universitas Muhammadiyah Surabaya, 2020)
Worming diseases are still a public health problem in Indonesia. This infection is still often found in cases in Southheast which is in Indonesia. Factors the geographical location on Indonesia,Which has a tropical climate and sufficient humidity, is very supportive for the development of parasites. Primary school age is a group that is often exposed to helminthiasis because is is often assosiated with soil contaminated with worm egg.This study aims to determine the prevalence of worm egg parasitic infections in the feses of student in grade 1 to grade 6 of the manyar sabrangan 231 surabaya elementary school in 2020.The research sample was faeses of grade student 1 – 6 Manyar Elementary school 231 Surabaya.Identification of worm eggs is carried out in E – Labz Telcomedika Surabaya Elementary. Data taken in the form of parasitic worm eggs based on morphological characteristics.From the result of study found in 240 elementary scholl children examined, as many as 29 children (12,1 %) positive for helminthiasis, with parasite rate of 18 children (7,5%) Ascaris lumbricoides, 7 children (2,92%) Trichiuris trichiura. The conclusion of this study, helminthiasis of student in grade 1 to grade 6 of the Manyar Sabrangan Surabaya Elementary School were found ,namely Ascaris lumbricoides,Trichiuris trichiura